Delphi consensus on bile duct injuries during laparoscopic cholecystectomy: an evolutionary cul‐de‐sac or the birth pangs of a new technical framework?. (23rd October 2017) - Iwashita, Yukio; Hibi, Taizo; Ohyama, Tetsuji; Umezawa, Akiko; Takada, Tadahiro; Strasberg, Steven M.; Asbun, Horacio J.; Pitt, Henry A.; Han, Ho‐Seong; Hwang, Tsann‐Long; Suzuki, Kenji; Yoon, Yoo‐Seok; et al.
Abstract: Bile duct injury (BDI) during laparoscopic cholecystectomy remains a serious iatrogenic surgical complication. BDI most often occurs as a result of misidentification of the anatomy; however, clinical evidence on its precise mechanism and surgeons' perceptions is scarce. Surgeons from Japan, Korea, Taiwan, and the USA, etc. ( n = 614) participated in a questionnaire regarding their BDI experience and near‐misses; and perceptions on landmarks, intraoperative findings, and surgical techniques. Respondents voted for a Delphi process and graded each item on a five‐point scale. The consensus was built when ≥80% of overall responses were 4 or 5. Response rates for the first‐ and second‐round Delphi were 60.6% and 74.9%, respectively. Misidentification of local anatomy accounted for 76.2% of BDI. Final consensus was reached on: (1) Effective retraction of the gallbladder, (2) Always obtaining critical view of safety, and (3) Avoiding excessive use of electrocautery/clipping as vital procedures; and (4) Calot's triangle area and (5) Critical view of safety as important landmarks. For (6) Impacted gallstone and (7) Severe fibrosis/scarring in Calot's triangle, bail‐out procedures may be indicated. A consensus was reached among expert surgeons on relevant landmarks and intraoperative findings and appropriate surgical techniques to avoid BDI. Abstract : Highlight Iwashita and colleagues conducted a two‐round Delphi process on bile duct injuries during laparoscopic cholecystectomy. 614 surgeons from Japan, Korea, Taiwan, the USA and other nations provided expert opinion on injury or near‐miss occurrence, risk management, and bailout procedures. Consensus was reached on appropriate bailout procedures and several other items.